Young adult simultaneous alcohol and marijuana use: Between- and within-person associations with negative alcohol-related consequences, mental health, and general health across two-years. (December 2021) - Fleming, Charles B.; Duckworth, Jennifer C.; Rhew, Isaac C.; Abdallah, Devon Alisa; Guttmannova, Katarina; Patrick, Megan E.; Lee, Christine M.
Highlights: SAM in more months was associated with more negative alcohol-related consequences. Negative alcohol-related consequences were more numerous in SAM use months. SAM was associated with worse mental and general health than alcohol-use-only. SAM was similar to other patterns with marijuana use in mental and general health. Abstract: Background: Simultaneous alcohol and marijuana use (SAM) may be linked to both short- and longer-term problems for young adults. Across two years of longitudinal data, we examined between- and monthly within-person associations of alcohol and marijuana use patterns, including SAM, with negative alcohol-related consequences, depressive symptoms, and general health. Methods: 773 young adults (aged 18–23 at screening; 56% women) who used alcohol in the year prior to study enrollment were surveyed monthly for 24 months. Multilevel models assessed associations of alcohol and marijuana use patterns with outcomes. Results: Individuals who reported a higher proportion of SAM months had more negative alcohol-related consequences (Rate Ratio [ RR ] = 1.49, 95% CI : 1.17, 1.89). At the within-person level, participants experienced more alcohol-related consequences on months when SAM was reported compared to months of alcohol-only ( RR = 1.17, 95% CI : 1.10, 1.25) and months of concurrent alcohol and marijuana use without simultaneous use (CAM; RR = 1.20, 95% CI : 1.11, 1.29). Compared to alcohol-only, SAM was associated with more depressive symptoms and poorer general health at the between-person level and with more depressive symptoms at the monthly within-person level; however, SAM did not differ substantially from using neither alcohol nor marijuana or CAM for these outcomes at either the between- or within-person level. Conclusions: SAM use may indicate risk for negative alcohol-related consequences, both within months of SAM use and across more extended time periods. Individuals who engage in SAM may experience worse mental and physical health than individuals who use alcohol exclusively.